2012
DOI: 10.1371/journal.pone.0044593
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Metabolizing Microbes Dominate Microbial Communities in Andesite-Hosted Shallow-Sea Hydrothermal Systems

Abstract: To determine microbial community composition, community spatial structure and possible key microbial processes in the shallow-sea hydrothermal vent systems off NE Taiwan’s coast, we examined the bacterial and archaeal communities of four samples collected from the water column extending over a redoxocline gradient of a yellow and four from a white hydrothermal vent. Ribosomal tag pyrosequencing based on DNA and RNA showed statistically significant differences between the bacterial and archaeal communities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 40 publications
(43 reference statements)
7
57
2
Order By: Relevance
“…A recent shallow-water pyrosquencing study in the Okinawa Trough found bacterial communities dominated by sulfur-metabolizing organisms. They found members of the genus Nautilia and Thiomicrospira as the major component of the two hydrothermal vents sampled (Zhang et al, 2012). Neither genus was found in our study.…”
Section: Comparison To Other Studiescontrasting
confidence: 51%
“…A recent shallow-water pyrosquencing study in the Okinawa Trough found bacterial communities dominated by sulfur-metabolizing organisms. They found members of the genus Nautilia and Thiomicrospira as the major component of the two hydrothermal vents sampled (Zhang et al, 2012). Neither genus was found in our study.…”
Section: Comparison To Other Studiescontrasting
confidence: 51%
“…According to 16S rRNA gene analysis, archaea related to methanogens and methanotrophs contribute to a much greater percentage of the total sequences in the deep-sea hydrothermal vent than in the shallow-sea hydrothermal system [13,17]. Deep-sea CH 4 -rich hydrothermal fluids support the growth of large methanogenic and methanotrophic communities, such as those in the Lost City chimneys [5,11].…”
Section: Resultsmentioning
confidence: 99%
“…pompejana episymbiont community belonged to Epsilonproteobacteria [6]. Previous studies showed that chemolithoautotrophs from Epsilonproteobacteria and Gammaproteobacteria are predominant primary producers in shallow-sea hydrothermal systems [13,17]. However, the 16S rRNA gene survey offered only limited information on the biogeographic patterns of microbial consortia within an environment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Sulfurimonas and Sulfurimonas are frequently detected at high abundances in diverse marine environments where strong gradients of oxygen and sulfide exist, including cold seep sediments (Roalkvam et al, 2011), waters of redoxclines (Grote et al, 2007), coastal marine sediments (Hoor, 1975), and both shallow and deep hydrothermal vents (Huber et al, 2010; Zhang et al, 2012). The primers do not detect Arcobacter , a genus within the Epsilonproteobacteria that also uses the Sox pathway.…”
Section: Discussionmentioning
confidence: 99%